Chemotherapy-resistant breast implant-associated anaplastic large cell lymphoma. (27th November 2013) - Parthasarathy, Muralidharan; Orrell, Julian; Mortimer, Caroline; Ball, Liz
Abstract : A 43-year-old woman presented with a few weeks' history of discomfort and swelling in her left breast. She had undergone bilateral breast augmentation 8 years previously. There were no risk factors for breast cancer. Clinical examination, mammography and breast ultrasound revealed a large left breast mass adjacent to the breast implant with enlarged axillary lymph nodes. Owing to diagnostic uncertainty, core biopsies were sent to a specialist unit which confirmed breast implant-associated anaplastic large cell lymphoma with involved lymph nodes. Staging investigations confirmed no distant disease. The lymphoma multidisciplinary team recommended cyclophosphamide, doxorubicin, vincristine and prednisone chemotherapy, followed by implant removal and local radiotherapy. However, the patient's disease progressed on first-line, and then second-line chemotherapy. She therefore had a mastectomy and axillary node clearance followed by radiotherapy, with a planned delayed left breast reconstruction and removal of the right breast implant.